Generalist-led hospital models and their alignment with value-based care: a systematic review protocol - Shankar, Ravi; Devi, Fiona; Mukhopadhyay, Amartya (BMJ open, 2025)
IntroductionValue-based care focuses on delivering high-quality care while managing costs. Generalist-led hospital models, with generalist physicians playing a central role, have emerged as an approach to achieve value-based care goals. However, the evidence on their effectiveness remains mixed. This systematic review will synthesise evidence on the impact of generalist-led models on patient outcomes, healthcare costs and resource utilisation compared with traditional models.Methods and analysisWe will search PubMed, Web of Science, Embase, CINAHL, Medline, Cochrane Library, PsycINFO and Scopus from inception to present for studies comparing generalist-led hospital models with traditional specialist-led or other models. Observational studies and randomised trials will be included. The primary outcomes are patient mortality, morbidity, satisfaction, healthcare costs, length of stay, readmissions and consultations. Two reviewers will independently screen studies, extract data and assess quality using the Newcastle-Ottawa Scale for observational studies and the Cochrane Risk of Bias tool for randomised trials. A narrative synthesis will be conducted, with a meta-analysis if appropriate. Grading of Recommendations Assessment, Development and Evaluation will assess certainty of evidence. Heterogeneity will be explored through subgroup analyses and meta-regression. The review will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Ethics and disseminationEthical approval is not required as this is a protocol for a systematic review with no primary data collection. The results will be disseminated through a peer-reviewed publication, conference presentations and stakeholder engagement activities.PROSPERO registration numberCRD42024600155.